A game analysis of MNC CSR in China - Ronald J. Salazar (Taylor & Francis Group, 2018)
Weakening multinational corporation (MNC) commitment to corporate social responsibility (CSR) has caused increasing concern in China. What motivates MNC’s to diminish their commitment to CSR? This paper applies game theory to attempt to answer this important question for the Chinese context. The aim of this paper is to characterize the decision choices MNC managers face using game theory and to evaluate whether game theory, based on cost–benefit analysis, can contribute to a better understanding of the tendency to diminish CSR. Public opinion, political legitimacy, competing priorities, stage of market development, short-term orientation, and stakeholder activism each influence manager’s choices. Despite the widespread recognition that CSR is important in business, the costs of CSR implementation are implicitly weighed against the benefits of favorable CSR outcomes. We demonstrate how the weakening observed in China exhibits properties amenable to analysis in a game-theoretic sense rather than dominance and how the trend might be reversed. The findings of this study provide useful insights into the consequences of stakeholder behavior for CSR outcomes. Researchers will find the results helpful in further exploring how specific stakeholder activities influence CSR. Investors, managers, regulators, and stakeholders will find the results expository of some underlying forces influencing managerial decision-making in MNCs.